Stroke after emergent surgery for acute type A aortic dissection: predictors, outcome and neurological recovery. (17th January 2018) - Dumfarth, Julia; Kofler, Markus; Stastny, Lukas; Plaikner, Michaela; Krapf, Christoph; Semsroth, Severin; Grimm, Michael
Abstract: OBJECTIVES: Despite improvement in operative and cerebral perfusion techniques, cerebral malperfusion and neurological injury remain a dreaded complication of acute type A aortic dissection. We aimed to identify predictors for postoperative stroke and analyse the impact on morbidity, neurological recovery and mid-term survival. METHODS: Between 2000 and 2017, 303 (71.9% men, mean age 58.9 ± 13.6 years) patients with acute type A aortic dissection underwent surgical repair. Clinical and imaging data were retrospectively evaluated. Patients were divided into 2 groups depending on the presence of postoperative stroke. RESULTS: Postoperative stroke was detected in 15.8% ( n = 48) of the patients. Patients with postoperative stroke showed higher rates of preoperative cardiopulmonary resuscitation (stroke: 18.8% vs no stroke: 3.5%, P < 0.001) and malperfusion syndrome (stroke: 47.9% vs no stroke: 22.4%, P < 0.001). Multivariable analysis identified the presence of bovine aortic arch [odds ratio (OR) 2.33, 95% confidence interval (CI) 1.086–4.998; P = 0.030], preoperative cardiopulmonary resuscitation (OR 6.483, 95% CI 1.522–27.616; P = 0.011) and preoperative malperfusion (OR 2.536, 95% CI 1.238–5.194; P = 0.011) as independent predictors for postoperative stroke. Postoperative stroke had a strong impact on morbidity and was associated with higher rates of postoperative complications and a significantly longer hospital stay (stroke: 23 ± 16 days vs no stroke: 17 ± 18 days, P = 0.021). Postoperative stroke was not independently associated with in-hospital mortality (adjusted OR 1.382, 95% CI 0.518–3.687; P = 0.518). There was no difference in mid-term survival between patients with stroke and patients without stroke. CONCLUSIONS: This study identified independent preoperative predictors for postoperative stroke. Although postoperative stroke was associated with significant morbidity and postoperative complications, significant impairment in mid-term survival could not be confirmed by the data.